Penerapan Information Adoption Model Untuk Mengukur Pengaruh Electronic Word Of Mouth Terhadap Niat Beli Scarlett Whitening di Media Sosial Tiktok - Iskamto, Dedi; Zumarnis, Silfadila (Ekonomis: Journal of Economics and Business, 2024)
Technological developments have increased from year to year, starting from the first industrial revolution technology 1.0 until now the ongoing revolution is named industry 4.0 by the World Economic Forum in 2016 which is called the digital era. The industrial revolution 4.0 involves all activities centered on the internet or often called the Internet of Things. TikTok has experienced a rapid increase where in 2022 it will be 61.3% of the total population and in 2021 it will be 38.7%. Based on these data, TikTok is the social media that has experienced the most rapid increase as the most active social media application in Indonesia. Scarlett Whitening is one of the most viewed brands on the Tiktok app. This study aims to better understand the effect of eWOM based on the TikTok application on Scarlett Whitening's purchase intention. To understand the impact of eWOM, I apply the information adoption model as a model that has been widely used in previous eWOM studies. Research using quantitative methods with the aim of this research is causal. Data collection used the non-probability sampling method with the convenience sampling type of 385 respondents using Scarlett. This study used a questionnaire data collection technique with a Likert scale and data analysis techniques using Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software.